Craniofacial and Craniocervical Features in Cartilage-Hair Hypoplasia: A Radiological Study of 17 Patients and 34 Controls - Arponen, Heidi; Evälahti, Marjut; Mäkitie, Outi (Frontiers in Endocrinology, 2021)
Biallelic mutations in the non-coding RNA gene RMRP cause Cartilage-hair hypoplasia (CHH), a rare skeletal dysplasia in which the main phenotypic characteristic is severe progressive growth retardation. This study compared the cranial dimensions of individuals with CHH to healthy subjects. Lateral skull radiographs of 17 patients with CHH (age range 10 to 59 years) and 34 healthy individuals (age range 10 to 54 years) were analyzed for relative position of the jaws to skull base, craniofacial height and depth, as well as vertical growth pattern of the lower jaw, anterior cranial base angle, and the relationship between the cervical spine and skull base. We found that the length of the upper and lower jaws, and clivus were significantly decreased in patients with CHH as compared to the controls. Anterior cranial base angle was large in patients with CHH. Basilar invagination was not found. This study found no severe craniofacial involvement of patients with CHH, except for the short jaws. Unexpectedly, mandibular deficiency did not lead to skeletal class II malocclusion. Although the jaws were shorter in patients with CHH, they were proportional to each other. A short posterior cranial base was not associated with craniocervical junction pathology.